Seleção de extratores químicos para avaliação da disponibilidade de zinco em solos do estado de São Paulo - Ferreira, M. E.; Dacruz, MCP (Empresa Brasileira de Pesquisa Agropecuária (EMBRAPA), 1992)
The purpose of this study was to evaluate methods for predicting availability of Zn in soils. Surface soil samples representing Podzolized soils from Lins and Marilia var. Marilia and var. Lins, medium texture Dark-Red Latosol, Dusky-Red Latosol and Terra Roxa Estruturada, were gathered from fields in Jaboticabal, SP, Brazil. Com was used as indicator plant in a greenhouse experiment. Availability of Zn was determined with: 0.5 M CaCl2, 2.0 N MgCl2, N CH3COONH4 (pH 6.0 and 4.8), 0.05 and 0.1 N HCl, 0.05 N H2SO4, 0.005 M DTPA (pH 7.3 and 6.0), 1.0% Na2-EDTA, 0.01 M EDTA + 1.0 M (NH4)2CO3 (pH 8.6) and 0.02 M EDTA + 0.5 M CH3COOH + 0.5 M CH3COONH4. By using the simple correlation coefficients (Zn extracted from soils x absorbed by plants it can be concluded that the complexant agents and acid solutions showed to be efficient. The salt solutions showed low extraction capacity, low correlation coefficients and less accuracy. By considering aspects as accuracy and easy management DTPA pH 7,3 and Na2-EDTA can be indicated as the most apropriates (r values, respectively, 0.873** and 0.868** and V.C. 7.52% and 7.98%).

Estudaram-se métodos para avaliação da disponibilidade de Zn empregando-se amostras da camada arável de solos pertencentes aos grandes grupos: Solos Podzolizados de Lins e Marília, var. Lins e var. Marília, Latossolo Vermelho-Escuro textura média, Latossolo Roxo e Terra Roxa Estruturada. O Zn foi extraído com: CaCl2 0,5 M, MgCl2 2,0 N, CH3 COONH4 1,0 N pH 4,8 e 6,0, HCl 0,05 N e 0,1 N, H2SO4 0,05 N, DTPA 0,005 M pH 7,3 e pH 6,0, Na2-EDTA 1,0%, EDTA 0,01 M + (NH4)2CO3 1,0 M pH 8,6 e EDTA 0,02 M + CH3COOH 0,5 M + CH3COONH4 0,5 M pH 4,65. No ensaio em casa de vegetação foi usado o milho. As soluções de agentes complexantes a as ácidas constituíram-se em extratores eficientes. As salinas apresentaram baixa capacidade de extração e conseqüentemente maior imprecisão. Considerando-se aspectos relacionados à simplicidade de manuseio e precisão, os extratores DTPA 0,005 M pH 7,3 e Na2-EDTA 1,0% podem ser indicados como mais apropriados (valores de C.V. iguais a 7,52% e 7,98% e de r, com Zn extraído pela planta a 0,873** e 0,868**).
Selection of chemical extractors for the evaluation of availability of zinc in soils in the state of Sao-Paulo, Brazil
Keywords: Soil fertility; SOIL TEST